Positive airway pressure adherence in pediatric obstructive sleep apnea: A systematic scoping review. (June 2020) - Watach, Alexa J.; Xanthopoulos, Melissa S.; Afolabi-Brown, Olufunke; Saconi, Bruno; Fox, Kathleen A.; Qiu, Maylene; Sawyer, Amy M.
Summary: Positive airway pressure (PAP) therapy is a commonly prescribed treatment for pediatric obstructive sleep apnea (OSA). Negative health consequences associated with untreated OSA make understanding the utilization of PAP therapy imperative. The aim of this review was to describe PAP use in children and adolescents with OSA, explore factors that influence use, and describe published scientific or clinical approaches to improve use. Among 20 studies, average PAP adherence was 56.9% (range, 24–87%). PAP use averaged 4.0 h (SD = 3.1) to 5.2 h (SD = 3.4) per night. Cautious consideration of summary estimates of PAP use is necessary as studies were heterogeneous and adherence definitions widely varied across studies. Age, sex, and developmental delay were the only factors associated with PAP use in more than one study. The majority of approaches to improve use were program evaluations rather than scientifically tested interventions. This review identified critical gaps in the existing literature and sets forth a research agenda for the future.